1996
DOI: 10.1074/jbc.271.1.153
|View full text |Cite
|
Sign up to set email alerts
|

The Affinity of Nuclear Factor 1 for Its DNA Site Is Drastically Reduced by Nucleosome Organization Irrespective of Its Rotational or Translational Position

Abstract: A DNA-bending sequence has been used for in vitro reconstitution of nucleosomes in order to direct a nuclear factor 1 (NF-1) binding site into different nucleosome positions. By this strategy nucleosomes were obtained that had one of two rotational positions of the NF-1 binding site, one oriented toward the periphery and the other toward the histone octamer, translationally positioned 50 and 45 base pairs, respectively, from the nucleosome dyad. The affinity of partially purified NF-1 for these nucleosomal tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…Previous work suggested that the nucleosome positioning is important for restricting the access of NF1, Oct1, and other basal factors to their cognate binding sites, as shown in vitro for NF1 (17,57,58). During hormone induction, it was assumed that the hormone-activated GR binds and mediates a chromatin-remodeling event that will then allow binding of NF1, Oct1, and other basal factors to the MMTV promoter.…”
Section: The Mechanism Of Nucleosome Positioning Of the Mmtv Ltr: Intmentioning
confidence: 99%
“…Previous work suggested that the nucleosome positioning is important for restricting the access of NF1, Oct1, and other basal factors to their cognate binding sites, as shown in vitro for NF1 (17,57,58). During hormone induction, it was assumed that the hormone-activated GR binds and mediates a chromatin-remodeling event that will then allow binding of NF1, Oct1, and other basal factors to the MMTV promoter.…”
Section: The Mechanism Of Nucleosome Positioning Of the Mmtv Ltr: Intmentioning
confidence: 99%
“…This results in a tighter chromatin structure which confers a more stringent repression of transcription than chromatin formed on DNA injected in the double-stranded form (2). Several studies suggest that chromatin acts both by excluding certain upstreamgene-specific transcription factors from their recognition sites (1,4) and by inhibiting access of the basic transcription machinery to the transcriptional initiation site (17,30,33,64).…”
mentioning
confidence: 99%
“…Activation of the MMTV promoter by steroid hormones is associated with a region-specific chromatin structural transition detected as an increase in sensitivity to nucleases (38,39), chemical probes (38), or restriction enzymes (1). This nucleoprotein remodeling event is implicated, in turn, in the secondary binding of transcription factors that are excluded by nonremodeled chromatin (2,4,8,22,37,(45)(46)(47).…”
mentioning
confidence: 99%
“…Glucocorticoid receptor (GR)-induced remodeling was originally associated with one nucleosome family (Nuc-B) in the LTR-phased array (1,4,22,37,38,46,47); four receptor binding sites are associated with this nucleosome family (Ϫ70 to Ϫ190). Recently, however, the region of GR-induced hypersensitivity has been found to extend upstream of the Nuc-B region to Ϫ295 (15).…”
mentioning
confidence: 99%